(untitled) (ZOO-Journal, 2019)
Data analysis tools and software have been increasing each day in the academic field. They were classified into two categories: one category of statistical tool that needs money to buy its licence to use and install into owns computer. Such software are called closed software. Another category of tool or software is called open source tool or open software. This later group comes freely and one can get licence freely. Academicians are free to choose one. Definitely ’R’ and its associated tools which we can download freely and use freely has no better alternatives. ’R’ users have been increasing rampantly these days in this world.